Cape Krusenstern National Monument, Alaska : draft general management plan and environmental assessment, land protection plan, wilderness suitability review. - United States. National Park Service. ([Washington, DC] : U.S. Department of the Interior, National Park Service : U.S. G.P.O., 1985)
"March 1985." Bibliography: p. 9/3-9/6. Mode of access: Internet.